1991
DOI: 10.21273/jashs.116.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Temperature Effects on Stem Elongation in Poinsettia

Abstract: Elongation characteristics of each internode on a lateral shoot of poinsettia (Euphorbia pulcherrima Klotz) `Annette Hegg Dark Red' were determined from pinching through anthesis for plants grown with 36 day/night temperature (DT/NT) combinations between 16 and 30C. The Richards function was used to describe the elongation of each internode. The first internode developing on a lateral shoot was longer and matured faster than subsequent internodes. The length of the first inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 7 publications
3
31
1
Order By: Relevance
“…Clarke, Xanthium strumarium L., Lycopersicon esculentum L., Z. mays, Salvia splendens F., Impatiens wallerana Hook, Nephrolepsis exaltata L., Fuchsia × hybrida Vilm. , Dendranthema × grandiflora Tzvelev, , Campanula isophylla Moretti (Moe and Heins, 1990;Moe et al, 1991), Euphorbia pulcherrima Klotz (Berghage and Heins, 1991), and L. longiflorum was best described by DIF, and increased as DIF increased. Likewise, dahlia was responsive to DIF, with primary shoot length linearly and positively related to DIF, except at and perhaps below NT of 10C (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Clarke, Xanthium strumarium L., Lycopersicon esculentum L., Z. mays, Salvia splendens F., Impatiens wallerana Hook, Nephrolepsis exaltata L., Fuchsia × hybrida Vilm. , Dendranthema × grandiflora Tzvelev, , Campanula isophylla Moretti (Moe and Heins, 1990;Moe et al, 1991), Euphorbia pulcherrima Klotz (Berghage and Heins, 1991), and L. longiflorum was best described by DIF, and increased as DIF increased. Likewise, dahlia was responsive to DIF, with primary shoot length linearly and positively related to DIF, except at and perhaps below NT of 10C (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…; Niu et al, 2000), and poinsettia (Euphorbia pulcherrima Willd. ex Klotz; Berghage and Heins, 1991). For example, Erwin et al (1989) reported that plant height of Easter lily increased by 129% as DIF increased from -16 to +16°C.…”
mentioning
confidence: 99%
“…Even if some parameters to some extent are given a biological interpretation (e.g. Berghage and Heins, 1991;Fisher, Heins and Lieth, 1996a), the danger of over-or underfitting to data is obvious, especially in view of the complexity of biological processes. With a softer model that adapts to data, and with a proper model selection procedure, we can choose the optimal model complexity for prediction given the available data.…”
Section: X2 Resultsmentioning
confidence: 99%